Les patients atteints d'hypertension artérielle: approche de leur vécu - Araujo Sadala, M. L.; Messias Mendes, I. (My University, 1998)
The study aims at exploring the experience of the patients suffering from high blood pressure, analysing the difficulties they evoke and trying to generate similarities. It is a qualitative study, based on the phenomenological method. The interviews highlight the fact that the patients are preoccupied only by the symptoms of high blood pressure. They also show that all the patients live through the disease with a lot of emotions, with feelings of frustration, stress, anxiety and helplessness. A better understanding of the patients' experience must enable the nurses to have better targeted actions.
Patients with arterial hypertension: approach to their experiences
Keywords: adaptive behavior; adult; attitude to health; daily life activity; human; hypertension; lifestyle; nursing; nursing methodology research; psychological aspect; questionnaire; Activities of Daily Living; Adaptation, Psychological; Adult; Attitude to Health; Humans; Hypertension; Life Style; Nursing Methodology Research; Questionnaires